Silicon Promotes Adventitious Shoot Regeneration and Enhances Salinity Tolerance of Ajuga multiflora Bunge by Altering Activity of Antioxidant Enzyme - Iyyakkannu Sivanesan; Byoung Ryong Jeong (The Scientific World Journal)
We investigated the effect of Si concentration on shoot regeneration and salinity tolerance of Ajuga multiflora. Addition of Si to the shoot induction medium significantly increased the frequency of shoot induction. The average number of shoots regenerated per explant decreased on the medium containing NaCl alone, while there was less decrease when the shoot induction medium was supplemented with both NaCl and Si. The shoot induction percentage increased linearly with increasing concentration of Si in the NaCl containing medium. Addition of Si to the shoot induction medium significantly increased SOD, POD, APX, and CAT activity in regenerated shoot buds as compared with the control. The inclusion of Si to the NaCl containing medium significantly increased the SOD activity in leaves and roots, while it decreased POD, APX, and CAT activity in both organs. Scanning electron microscopic analysis showed that there are no distinct differences in the structure of stomata between the control and Si-treated plants. However, NaCl treatment significantly affected the structure and number of stomata as compared to the control. Wavelength dispersive X-ray analysis confirmed the high Si deposition in trichomes of plants grown in the Si containing medium but not in plants grown in the medium without Si.